Analisis Produk Domestik Regional Bruto Terhadap Penyerapan Tenaga Kerja Provinsi Jawa Timur - Kesumawati, Fitria Oktaviana; Fisabilillah, Ladi Wajuba Perdini (Jurnal Ekonomika : INDEPENDEN, 2024)
This study aims to analyze the influence of Gross Regional Domestic Product (GRDP) on labor absorption in East Java Province. GRDP is an important indicator that reflects the economic level of a region and is expected to have a significant relationship with the level of labor absorption. The method used in this study is simple linear regression analysis with secondary data obtained from the Central Statistics Agency (BPS) of East Java Province over a certain period. The results of the study indicate that there is a positive and significant relationship between GRDP and labor absorption in East Java Province. Every increase in GRDP is followed by an increase in the number of absorbed workers. These findings indicate that economic growth in East Java can create job opportunities and reduce the unemployment rate. Therefore, policies that support the increase of GRDP, such as investment in productive sectors and infrastructure improvement, are crucial to be continuously developed in order to enhance community welfare through increased labor absorption. Keywords: Gross Regional Domestic Product (GRDP), Employment Absorption